A Model of Pedometer Determined Physical Activity in Primary School Children - Zanevskyy, Ihor; Bodnarchuk, Olena (Physical Education Theory and Methodology, 2020)
The purpose of this research is to create a model of interaction between steps/day counts regarding genders, seasons of a year, and days of week. Material and Methods. Totally 74 of 4-th grade pupils (38 boys and 36 girls) from three primary schools in the industrial city were involved into the pedometer investigation. All the students were good healthy, and they participated in the schools’ lessons of physical education according to the common program. Pedometer determined physical activity was measured during a day using fitness tracker band. The measurements were done during one academic year using three full weeks (a week in autumn, winter, and spring). ANOVA was used to determine differences between samples grouped according days of weeks. Results. A strong significant difference between counts of steps during days of week for boys (p = 0.006) and smaller for girls (p = 0.052) were discovered with corresponding parts in the total variation (62.5 and 46.0 %). The same significant differences were discovered between mean counts in seasons (p = 0.053, 0.037) with corresponding parts in the total variation (14.5, 22.8 %). Rather significant variations of interaction between days of week and mean season results took place for boys (23.0%) as well for girls (31.1 %). Conclusions. During evaluation of physical activity in children based on steps/day counts, interaction between gender, season, and day of week should be taken into consideration.